Sustainable effective use of brackish and canal water for rice-wheat crop production and soil health - Khalil AHMED; Amar Iqbal SAQIB; Ghulam QADIR; Muhammad Qaisar NAWAZ; Muhammad RIZWAN; Syed Saqlain HUSSAIN; Muhammad IRFAN; Muhammad Mohsin ALI (Acta Agriculturae Slovenica)
A pot study was conducted to develop reasonable irrigation scheduling methods for rice-wheat crop rotation by conjunctive use of low-quality brackish water and good quality canal water. Treatments tested were; T1 (canal water), T2 (brackish water), T3 (brackish water for rice and canal water for wheat), T4 (last two irrigations to rice, and initial two irrigations to wheat with canal water), T5 (last two irrigations to rice but two initial and one last irrigation to wheat with canal water). Results revealed that irrigation with canal water resulted in the maximum mean biomass and grain yield of rice and wheat crops followed by cyclic use of brackish and canal water. While continuous irrigation with brackish water resulted the lowest mean biomass and grain yield. The different modes of irrigations also influenced chemical properties of soil, brackish water adversely affected the soil properties, and maximum pH of soil saturated paste (pHs), electrical conductivity of soil extract (ECe) and sodium adsorption ratio (SAR) were recorded where brackish water was used continuously. Therefore, it was concluded that when water is valuable and freshwater resources are limited, cyclic use of the canal and brackish water is also profitable with marginal effect on biomass and grain yield and proves least detrimental for soil health.